FOREST PRODUCTS RESEARCHES IN THE WORLD: FROM LJUBLJANA UP TO SALT LAKE CITY - Shalaev, Valentin (Innovation in Woodworking Industry and Engineering design, 2015)
The International Union of Forest Research Organizations (IUFRO) is well known all over the world. It is the oldest and largest organization, which combines forces for about 15 thousand scientists from different countries and regions. The Fifth Division „Forest Products“ is rather significant among IUFRO nine Divisions. This paper examines the scientific directions of the researches, which are the closest to Fifth Division in IUFRO „Forest Product“. They are: the report „Future research in forest products“ by Walter Liese at the XVIII IUFRO World Congress in 1986 in Ljubljana and the report „Forest Products Research in IUFRO: History and Future in Meeting’s Needs“ by Robert Youngs and John Youngquist at the XXI IUFRO World Congress in 2000 in Malaysia. The wide range of active performing 32 working and special research groups reflects the totality of scientific researches made by leading scientists of the international scientist community working on the subject. The agenda of the XXIV IUFRO World Congress (Salt Lake City, USA) and Strategy on 2015-2019 „Intrerconnecting forests, science and people“ emphasizes the significance of this research trend in forest products and in the most general form it determines the dynamics of their development.